The Determination of Best Fishing Gear for Small Pelagic Fisheries at Central Bangka Regency, Bangka Belitung Islands Province - Dareen Nadya Rema; Mulyono Sumitro Baskoro; Mohammad Imron; Muhammad Johar Rudin (Bogor Agricultural University, 2022)
The potential condition of fishery sector is indeed quite large in Central Bangka Regency. The majority of fishermen in Central Bangka Regency still use traditional fishing gear and simple fishing technology. The number of fishing units used in Central Bangka Regency consists of 370 units of lift net, 1,085 units of gillnets, 129 units of bubu, 60 units of sero, 125 units of fishing rods and 4 beach seines with a fleet of 1,767 (DKP Central Bangka Regency 2019). These types of fishing gear need to be assessed for performance and selected for superior fishing units as a form of optimizing to find out the strategy for developing appropriate and superior fishing units for the fisheries sector in the mining sector in Central Bangka Regency. The method of collecting data on fishing units was carried out by accidental sampling. The number of samples taken according to the category of fishing units were 20 units of lift net, 58 units of gill nets, 8 units of bubu, 3 units of sero, 10 units of fishing rods and 1 beach seines. Based on the results of standardization of technical aspects, environmental aspects, social aspects and economic aspects, the analysis of fishing gear gillnets is the most appropriate fishing gear to be developed in Central Bangka Regency with VA = 13.26 which makes gillnets gear priority I. Priority fishing gear II is a fishing rod with VA = 12.87 and priority III is a lift net with VA = 11.56. Keywords: superior fishing gear, sustainable fishing, Central Bangka Regency